The legacy of compliant activism in autocracies: post-Communist experience. Issue 2 (3rd April 2017) - Libman, Alexander; Kozlov, Vladimir
ABSTRACT: Compliant activism – that is, political activity of the population, either fully supporting the regime, or merely criticizing individual shortcomings of its policies – strengthens authoritarian rule. However, compliant activism can over time turn into non-compliant one. Hence, the regimes need to ensure that the norms of compliant activism are internalized by the society and become self-enforcing. We use the case of the Communist legacies in Russia to show that compliant activism can, indeed, become highly persistent and outlive the regime, where it emerged. Using cross-regional variation in the levels of compliant activism in the contemporary Russia, we demonstrate that it is strongly affected by the variation in the membership share of the Communist Party of the Soviet Union in the 1970s. The results have broader implications beyond the Russian case and provide relevant insights for studying political activism in autocracies.